মুজিবনগরের গ্রামীন চর্মকার সম্প্রদায় : সামাজিক অসমতা ও মিথস্ক্রিয়া - আলি, এ. এফ. ইমাম; রশিদ, মোঃ মজনুর (ঢাকা : নভেল পাবলিশিং, 2016)
Study on the caste system and social inequality between various castes in Mujibnagar of Bangladesh.
Includes bibliographical references.
In Bengali.
Keywords: Caste -- Bangladesh -- Mujibnagar; Equality -- Bangladesh -- Mujibnagar; Mujibnagar (Bangladesh) -- Social conditions